2010
DOI: 10.1177/0018726709343654
|View full text |Cite
|
Sign up to set email alerts
|

Context, strategy and financial participation: A comparative analysis

Abstract: This article investigates where financial participation is most likely to be encountered, and explores its compatibility with collective forms of employee voice. It is based on the findings of a major international survey of human resource management (HRM) practices. We found that financial participation was not affected by collective employee voice, but that national context and associated HRM strategies had significant effects on its nature and extent. As financial participation is likely to make for greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 52 publications
4
26
0
Order By: Relevance
“…In our study, some evidence for complementarity was there for profit-sharing, but not for share ownership, which corresponds to what Poutsma et al (2006) and Croucher et al (2010) have found. In those companies where profit-sharing was introduced, employees were more often informed and consulted on strategic issues such as prospective decisions on organisational structure or work organisation.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In our study, some evidence for complementarity was there for profit-sharing, but not for share ownership, which corresponds to what Poutsma et al (2006) and Croucher et al (2010) have found. In those companies where profit-sharing was introduced, employees were more often informed and consulted on strategic issues such as prospective decisions on organisational structure or work organisation.…”
Section: Discussionsupporting
confidence: 81%
“…The evidence tends to support the view that the bigger the company the more likely it is that profit-sharing or share ownership is enabled for employees (Croucher et al, 2010;Festing et al, 1999;Gevers and Cludts, 2002;. The study by Welz and Fernandez-Macias (2008) covering 27 EU countries revealed that in bigger companies the likelihood of the incidence of financial participation was as much as four times higher compared to smaller companies.…”
Section: The Effect Of the Organisation Sizementioning
confidence: 92%
See 2 more Smart Citations
“…For instance, at the organizational level, organizational practices (e.g., employee participation, empowerment) and contexts (e.g., trustworthy climate, span of control) alter the effectiveness of employee stock ownership (Blasi, Freeman, & Kruse, 2016; A. M. Robinson & Wilson, 2006). At the country level, institutional contexts such as (de)centralization of pay determination and collective bargaining coverage affect the adoption (Croucher, Brookes, Wood, & Brewster, 2010;Kalmi, Pendleton, & Poutsma, 2012) and the effectiveness (Williams, 2018) of employee stock ownership.…”
mentioning
confidence: 99%